مذاهب الأئمة في الاحتجاج بالحديث المرسل وأثره في استنباطالأحكام الفقهيةرسالة مقدمة إلى برنامج ماجستير الشريعة الإسلامية بجامعة سوراكرتا المحمديةقسم : أصول الفقهMadzahib al-aimah fil al-ihtijaj bilhadist al-mursal wa arsaruhu fi istimbath al-ahkam al-fiqiyaah - Rijal, Ahmad; , Dr. M. Muinudinillah Basri, M.A (2014)
Hadith Mursal are hadith whose validity is still disputable as legitimation among scholars, since they fall to category of hadith dho'if (weak). Therefrom, several scholars argued that we might use them for hujjah mutlaq ( absolute argumentation), while some others said it might be wiser not to use them at all. Yet there is also another opinions which said it could be used under special conditions. Based on this, this study aims to uncover and shed light the disagreements above scientifically, as well as to find he differences and the influence of the jurisprudence of law-making (fiqh). Then, the researchers sought to raise a strong opinion based on the arguments presented in the thesis, so that the researchers and or anyone who wants to practice the Hadith Mursal can understand it properly. In this research, the author applied literature study method (qualitative), by collecting various references associated with the object of the research, and then reviewing, analyzing also comparing with the existing writings. At the end of the chapter authors come to the conclusion that Hadith Mursal might be used as long as the rawi (taler) is credible, selective, and do not make it easier in terms of not mentioning (throw) the rawi (taler) above /before him unless the scholars have been convinced that he was also a trusted one. There is difference of opinion among the scholars about the effects caused by the disputes scholars had themselves against the validity of Hadith Mursal. In this case there are two opinions: first, that the difference is only at the level of language expression which is not consequential on the jurisprudence of law making. Second, the difference is haqiqi which will have consequences to the law-making jurisprudence